Severe diabetic papillopathy mimicking non-ar... [Med J Malaysia. 2012] - PubMed - NCBI - Mallika, P.S; Aziz, S; Asok, T.; Chong, M.S; Tan, A.K; Chua, C.N (Medical Journal Malaysia, 2012)
Mallika PS, Aziz S, Asok T, Chong MS, Tan AK, Chua CN.